1992
DOI: 10.1016/0022-4804(92)90076-c
|View full text |Cite
|
Sign up to set email alerts
|

An improved method of in vivo wound disruption and measurement

Abstract: Biomechanical studies of wound strength are important because of new investigations in growth factors, cytokines, and fetal wounds. We compared two traditional methods of wound disruption measurement with a novel computerized model designed for in vivo experiments. An Instron tensiometer (INSTS) and an air insufflated positive pressure device (AIPPD) were compared with a vacuum-controlled wound chamber device (VCWCD). The VCWCD produced vacuum at the wound site and wound disruption was monitored with two video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…n = 6-7 different animals in each group after injury; however, wound strength returns to 80-90% of the baseline level only after 6 weeks [19]. Creation of a full-thickness incisional wound in mice or rats represents a clinically compatible experimental model in studying wound tensile strength [20]. Three days after injury, breaking strength and tissue levels of collagen in the healing incisional wound were significantly increased in comparison to an open wound [21].…”
Section: Discussionmentioning
confidence: 99%
“…n = 6-7 different animals in each group after injury; however, wound strength returns to 80-90% of the baseline level only after 6 weeks [19]. Creation of a full-thickness incisional wound in mice or rats represents a clinically compatible experimental model in studying wound tensile strength [20]. Three days after injury, breaking strength and tissue levels of collagen in the healing incisional wound were significantly increased in comparison to an open wound [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen young female Sprague-Dawley rats weighing 250 -350 g were used in this study. The rat was chosen because it has been well described in prior incisional wound-bursting strength studies (7)(8)(9). Animals were given a standard diet ad lib several days before the investigation.…”
Section: Animals and Settingmentioning
confidence: 99%
“…3 Prior studies have demonstrated that the octyl-cyanoacrylate-based adhesives are stronger than the butylcyanoacrylate-based adhesives. 7,8 A study comparing the bursting strength of incisional rat wounds closed with D and H found that the octyl-cyanoacrylate-based adhesive (D) was roughly three times stronger than the butyl-cyanoacrylate-based adhesive (H). 7 A similar study found that the WBS of D was significantly greater than that of the butyl-cyanoacrylate I (difference 98 mm Hg [95% CI = 32 to 165]).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A study comparing the bursting strength of incisional rat wounds closed with D and H found that the octyl-cyanoacrylate-based adhesive (D) was roughly three times stronger than the butyl-cyanoacrylate-based adhesive (H). 7 A similar study found that the WBS of D was significantly greater than that of the butyl-cyanoacrylate I (difference 98 mm Hg [95% CI = 32 to 165]). 8 However, both of these studies measured WBS only immediately after wound closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation